Effective utilization of infectious disease surveillance system in China: a literature study-based analysis - Yi-ming HU; Pei-wu SHI; Qun-hong SHEN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze current situation, development trend and regional disparity about effective utilization of infectious disease surveillance system and the effect of the utilization on infectious disease prevention and control in China. MethodsRelevant literatures and reports on infectious disease risk monitoring and early warning issued during 2004 - 2019 by infectious disease surveillance system in 31 provincial-level administrative divisions in China were systemically retrieved through searching websites of governmental agencies, professional organizations, China National Knowledge Infrastructure and Web of Science. The data on infectious disease incidence were extracted from China Health Statistics Yearbook for years from 2005 to 2020. The information collected were quantitatively analyzed to assess effective utilization of the infectious disease monitoring system. Spearman correlation and linear regression were adopted to explore the association of effective utilization of surveillance systems and infectious disease morbidity. ResultsThe average index for countrywide effective utilization of infectious disease surveillance system was 9.64% in 2019, with an increment of 1 338.81% compared with that in 2004; the average index for eastern region was relatively higher (11.73%) than that for other regions of China. Correlation and regression analysis showed that there was a reverse correlation between the effective utilization of infectious disease surveillance system and the incidence of infectious diseases at regional and national level, with the nationwide correlation coefficient of − 0.88 (P < 0.01) and standardized regression coefficient of − 6.87 (P < 0.001). ConclusionThe utilization of infectious disease surveillance system has been improved steadily during 2004 - 2019 in China, but regional difference for the utilization still exists and continuous efforts should be made for effective utilization of the surveillance system.